KEBIJAKAN TAHUN PEMBINAAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada UMKM Di KPP Pratama Candisari Semarang) - Yuli Widiastuti, 12.05.52.0053; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2016)
This study aims to analyze program TPWP on the tax compliance in KPP Pratama Candisari Semarang. The population in this study are personal tax payers list in KPP Pratama Candisari Semarang that have UMKM. Sampling was done using purposive sampling method and sample size of 105 respondens. Consisting of 105 personal tax payers list in KPP Pratama Candisari Semarang that have UMKM. The primary data using multiple liniear regression model. The result showed that the benefits of NPWP and TPWP and no significant positive effect on the tax compliance. The tax penalties and no significant negative on the tax compliance. The tax penalties and a significant positive on the willingness to pay taxes. The willingness to pay taxes and a significant positive on the tax compliance.Keywords: Tax Compliance, Willingness To Pay Taxes, Benefits Of TIN, Tax Penalties, TPWP